Survivin -31G>C polymorphism and gastrointestinal tract cancer risk: a meta-analysis. - Yan Liu; Lin Li; Haiyan Qi; Yan Gao; Sha Liu; Chongan Xu (PLoS ONE)
Background Emerging evidence showed that common functional -31G>C polymorphism (rs9904341 G>C) in the promoter region of the survivin gene is involved in the regulation of survivin expression, thus increasing an individual's susceptibility to gastrointestinal tract (GIT) cancer; but individually published results are inconclusive. The aim of this systematic review and meta-analysis was to derive a more precise estimation of the association between survivin -31G>C polymorphism and GIT cancer risk. Methods A literature search of PubMed, Embase, Web of Science and CBM databases was conducted from inception through July 1st, 2012. Crude odds ratios (ORs) with 95% confidence intervals (CIs) were used to assess the strength of association. Results Nine case-control studies were included with a total of 2,231 GIT cancer cases and 2,287 healthy controls. The results indicated that survivin -31G>C polymorphism was associated with increased risk of GIT cancer. In the stratified analysis by cancer types, significant associations were observed between survivin -31G>C polymorphism and increased risk of colorectal and gastric cancers. However, the lack of association of survivin -31G>C polymorphism with esophageal cancer risk may be due to a lack of a sufficient number of eligible studies and the influence of different genetic and environmental factors. Conclusion Results from the current meta-analysis suggests that survivin -31G>C polymorphism might increase the risk of GIT cancer, especially among gastric and colorectal cancers.